Foot posture index and hip joint rotation mobility in handball and soccer players - Brezovar, Tjaž (Annales kinesiologiae (Koper), 2023)
Purpose: To assess the foot posture and hip joint mobility of elite handball and soccer players and to investigate possible correlations between these measurements. Methods: We compared the differences in means of Foot Posture Index (FPI), pas-sive hip internal (IR), and external (ER) rotation range of motion (ROM) between three groups of male subjects (17 handball players, 17 soccer players, and 16 non-athletes). The Kruskal-Walli’s test and post-hoc pairwise comparison with the Mann-Whitney U test were used to determine the differences between the group means, and associations between variables were analyzed with Spearman’s correlation coefficient. Results: No significant differences in the mean FPI were found between the soccer players (1.3 ± 2.9), handball players (0.7 ± 2.1), and the control group (1.7 ± 2.5) (p > 0.05). Similarly, no significant difference was found between the groups in the hip ER ROM. In contrast, a significantly lower (p < 0.05) hip IR ROM was observed in the soccer players (30.6° ± 5.3°) compared to the handball players (41.0° ± 8.1°) and the control group (41.1° ± 6.4°). A weak positive correlation was only observed between the FPI and hip IR ROM in the soccer players (?: 0.36, p = 0.035). Conclusions: Handball and soccer players show a tendency toward less pronated feet compared to non-athletes, but the differences are not significant and the mean FPI values are still within the range of normal foot posture. The range of hip IR seems to be reduced in soccer players and weakly, but significantly and positively associated with the FPI value, which needs to be further investigated in future studies.
Keywords: foot shape; gibljivost kolka; handball players; hip mobility; nogometaši; oblika stopala; rokometaši; soccer players